A frog's head, old ashtrays and student politics - Jessie Waibauru (Asia Pacific Network, 1994)
Uni Tavur, the journalism training newspaper produced by the University of Papua New Guinea reporters and editors, celebrated its second decade of publishing in July 1994. The newspaper marked the occasion with a 20-page souvenir issue and made a television documentary.